Combating bone marrow failure with polymer materials - Koch, Kayla C.; Jadon, Nidhi; Thesmar, Iris; Tew, Gregory N.; Minter, Lisa M. (Frontiers in Immunology, 2024)
Bone marrow failure (BMF) has become one of the most studied autoimmune disorders, particularly due to its prevalence both as an inherited disease, but also as a result of chemotherapies. BMF is associated with severe symptoms such as bleeding episodes and susceptibility to infections, and often has underlying characteristics, such as anemia, thrombocytopenia, and neutropenia. The current treatment landscape for BMF requires stem cell transplantation or chemotherapies to induce immune suppression. However, there is limited donor cell availability or dose related toxicity associated with these treatments. Optimizing these treatments has become a necessity. Polymer-based materials have become increasingly popular, as current research efforts are focused on synthesizing novel cell matrices for stem cell expansion to solve limited donor cell availability, as well as applying polymer delivery vehicles to intracellularly deliver cargo that can aid in immunosuppression. Here, we discuss the importance and impact of polymer materials to enhance therapeutics in the context of BMF.